Physiotherapy students' experiences in implementing a health education programme - J.M. Frantz (AOSIS, 2010)
The skills required to educate and train the public with the properskills needed to care for themselves through the use of lifestyle modifications arenow becoming an important issue in health professions education. Integration ofhealth promotion in physiotherapy practice has been recommended and implemented.A  qualitative design using open ended questions was used to determine the experiencesof third year physiotherapy students at a local university in the Western Cape inimplementing a health education programme relating to chronic diseases of lifestyle in schools. The evaluation wasconducted at the end of the 5 week intervention programme. The intervention programme focused on providing highschool learners with knowledge regarding risk factors for chronic diseases of lifestyle. The information for each question was recorded from each student's response independently and coded according to similarities which finallytranslated into themes. The study highlighted that students needed more practical exposure to health education initia-tives within the clinical programme. It also created the awareness of the personal skills that students develop whenimplementing health education programmes. The implementation of health education programmes by physiotherapistsis a reality and the need to provide students with the relevant experience in various settings is essential.